Setting a New Course in Native American Protest Movements : The Menominee Warrior Society’s Takeover of the Alexian Brothers Novitiate in 1975 - Turner, Patricia R.; Sturtevant, Andrew; Moody, Heather Ann; Lavender, Rachel (My University, 2018)
This research seeks to understand the effect that the Menominee Warrior Society’s takeover of the Alexian Brothers Novitiate on future Native American protest movements. These movements came from two different strains of thought. The first was that of forceful action, or tactics, while the second was that of peaceful change through legislation, or strategies. The conflict between the two, culminated during the takeover, shaping the future of native American movements. This research examines these two strains and how they collided head on in the takeover. While others have written about the takeover in the context of a history of the tribe, I examine the takeover in the context of other native American movements of its kind. This research was conducted using primary documents and supported with a variety of scholarly secondary sources. I seek to show that the Menominee Warrior Society’s takeover of the Alexian Brothers Novitiate changed the way that future native American protest movements were conducted, using both strains of thought and ideology side by side, working together to create a more successful and positive product.
Color poster with text, map, and photographs.
Keywords: Menominee Indians; Protest movements; Posters